Electron mean free path dependence of the vortex surface impedance. (17th January 2017) - Checchin, M; Martinello, M; Grassellino, A; Romanenko, A; Zasadzinski, J F
Abstract: In the present study the radio-frequency complex response of trapped vortices in superconductors is calculated and compared to experimental data previously published. The motion equation for a magnetic flux line is solved assuming a bi-dimensional and mean-free-path-dependent Lorentzian-shaped pinning potential. The resulting surface resistance shows the unprecedented bell-shaped trend as a function of the mean-free-path observed in our previous experimental work. We demonstrate that such bell-shaped trend of the surface resistance as a function of the mean-free-path may be described as the interplay of the two limiting regimes of the surface resistance, for low and large mean-free-path values: pinning and flux-flow regimes respectively. Since the possibility of defining the pinning potential at different locations from the surface and with different strengths, we discuss how the surface resistance is affected by different configurations of pinning sites. By tackling the frequency dependence of the surface resistance, we also demonstrate that the separation between pinning- and flux-flow-dominated regimes cannot be determined only by the depinning frequency. The dissipation regime can be tuned either by acting on the frequency or on the mean-free-path value.